WHEN ENGLISH RINGS A BELL -2017 REVISED VERSION- IS IT A GOOD BOOK? - Beby Maharani Masyitha; Shelly Cardina Dona Artha; Ratri Handayani (Journal of English Education, 2018)
Coursebook is seen as a complete package of instructional material for teaching and learning process. It provides a framework for teachers, learning objectives and source of materials for students. In relation to this matter, this study exposed the analysis of English course book namely When English Rings a Bell (2017 Revised Version). The analysis was focused on the content of the course book to see if it matched the newest curriculum applied in Indonesia and can facilitate the English teaching process in grade seven. Checklist method was chosen since it was easier to be developed and more practical to be used. The checklist developed covered the relevance of the materials to the curriculum and syllabus, topic, language skills, supporting learning materials, language, and practical activities.